2010
DOI: 10.1021/ic100120d
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Exchange Coupling in f-Ion Pairs Using the Diamagnetic Substitution Method

Abstract: One of the challenges in the chemistry of actinide and lanthanide (f-ion) is quantifying exchange coupling between f-ions. While qualitative information about exchange coupling may be readily obtained using the diamagnetic substitution approach, obtaining quantitative information is much more difficult. This article describes how exchange coupling may be quantified using the susceptibility of a magnetically isolated analog, as in the diamagnetic substitution approach, along with the anisotropy of the ground st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 53 publications
3
45
0
Order By: Relevance
“…5), but to simulate the low temperature w M T(T) and M(H) data, we need to account for a weak exchange interaction. One way to simulate such thermodynamic data for orbitally degenerate ions is the Lines model 27 , which employs an isotropic exchange between the spin component of the angular momenta (S ¼ 5 / 2 for Dy(III); see Methods) and has been used previously to model interactions between lanthanides 15,28 . Employing this model with PHI 29 we find J Lines ¼ þ 0.047(1) cm À 1 , which gives excellent fits to both w M T(T) and M(H) (Fig.…”
Section: Synthesismentioning
confidence: 99%
“…5), but to simulate the low temperature w M T(T) and M(H) data, we need to account for a weak exchange interaction. One way to simulate such thermodynamic data for orbitally degenerate ions is the Lines model 27 , which employs an isotropic exchange between the spin component of the angular momenta (S ¼ 5 / 2 for Dy(III); see Methods) and has been used previously to model interactions between lanthanides 15,28 . Employing this model with PHI 29 we find J Lines ¼ þ 0.047(1) cm À 1 , which gives excellent fits to both w M T(T) and M(H) (Fig.…”
Section: Synthesismentioning
confidence: 99%
“…19 Since the structures of 3 + I -and 3 are almost identical, the complexes must have similar ligand fields, and the g-values of 3 + I -should be good estimates for those of 3. In this way, the information about the ligand field and unquenched orbital angular momentum of 3 needed for eqn 2 is obtained from its diamagnetic substitute, 3 + I -.…”
Section: Exchange Coupling In Lanthanide Single Molecule Magnets (1)mentioning
confidence: 99%
“…In this way, the information about the ligand field and unquenched orbital angular momentum of 3 needed for eqn 2 is obtained from its diamagnetic substitute, 3 + I -. 19,37 Using χ TIP and the g-values of 3 + I -, eqn 2 yields 2J = -0.11(2) eV or -920(180) cm -1 . This surprisingly large value is consistent with the large value predicted computationally.…”
Section: Exchange Coupling In Lanthanide Single Molecule Magnets (1)mentioning
confidence: 99%
“…Interestingly, these mixed d-f complexes allow the use of the so-called diamagnetic substitution approach, where the transition paramagnetic ion exchange-coupled to the lanthanide ion is substituted with a diamagnetic analogue, at the same time keeping the integrity of the crystal structure. This particular approach provides a qualitative picture of the relative magnitude of the active interactions in the system [6,7] which was particularly precious in the absence of reliable theoretical methods to evaluate them.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed view of the coordination sphere of the Dy III center is reported as reference in Figure 1: Dy III coordination number is eight, and analysis of the coordination polyhedron via use of SHAPE [18] provided evidence of a geometry intermediate between square antiprismatic, bicapped trigonal prismatic and trigonal dodecahedron geometry (see Table S1). The analysis of the packing, as well as detailed X-ray investigation on isostructural systems, [19] showed the existence of a 3D network made up of Dy III -Co III dinuclear entities where the five terminal CN groups of the {Co(CN) 6 } fragment are connected through hydrogen bonds to the Lncoordinated water molecules via crystallization water molecules. The static magnetic properties revealed that this network of hydrogen bonding interaction might result in non-negligible interdimer coupling interactions [17].…”
Section: Introductionmentioning
confidence: 99%